Role of aminoglycoside-modifying enzymes and 16S rRNA methylase (ArmA) in resistance of Acinetobacter baumannii clinical isolates against aminoglycosides - Maryam Asadi Jouybari; Mohammad Ahanjan; Bahman Mirzaei; Hamid Reza Goli (Revista da Sociedade Brasileira de Medicina Tropical, 2021)
Abstract INTRODUCTION: This study aimed to determine the role of genes encoding aminoglycoside-modifying enzymes (AMEs) and 16S rRNA methylase (ArmA) in Acinetobacter baumannii clinical isolates. METHODS: We collected 100 clinical isolates of A. baumannii and identified and confirmed them using microbiological tests and assessment of the OXA-51 gene. Antibiotic susceptibility testing was carried out using disk agar diffusion and micro-broth dilution methods. The presence of AME genes and ArmA was detected by PCR and multiplex PCR. RESULTS: The most and least effective antibiotics in this study were netilmicin and ciprofloxacin with 68% and 100% resistance rates, respectively. According to the minimum inhibitory concentration test, 94% of the isolates were resistant to gentamicin, tobramycin, and streptomycin, while the highest susceptibility (20%) was observed against netilmicin. The proportion of strains harboring the aminoglycoside resistance genes was as follows: APH(3′)-VIa (aphA6) (77%), ANT(2”)-Ia (aadB) (73%), ANT(3”)-Ia (aadA1) (33%), AAC(6′)-Ib (aacA4) (33%), ArmA (22%), and AAC(3)-IIa (aacC2) (19%). Among the 22 gene profiles detected in this study, the most prevalent profiles included APH(3′)-VIa + ANT(2”)-Ia (39 isolates, 100% of which were kanamycin-resistant), and AAC(3)-IIa + AAC(6′)-Ib + ANT(3”)-Ia + APH(3′)-VIa + ANT(2”)-Ia (14 isolates, all of which were resistant to gentamicin, kanamycin, and streptomycin). CONCLUSIONS: High minimum inhibitory concentration of aminoglycosides in isolates with the simultaneous presence of AME- and ArmA-encoding genes indicated the importance of these genes in resistance to aminoglycosides. However, control of their spread could be effective in the treatment of infections caused by A. baumannii.